0.9% Saline Induced Hyperchloremic Acidosis. Issue 2 (March 2015) - Barker, Megan E.
<x xml:space="preserve">Abstract</x> In the acute care setting, the type and amount of fluid administered has a significant impact on patient outcomes. In particular, 0.9% saline infusions are known to cause or exacerbate hyperchloremia. The studies presented evaluate possible complications from 0.9% saline infusions. These studies compared administration of 0.9% saline with lactated ringer or plasmalyte in the acute care setting. In each trial, the patients who were randomized to receive 0.9% saline infusions had a more severe acidosis from increased serum chloride levels. From the available data, chloride-restrictive intravenous fluid such as plasmalyte appears to reduce acid-base disturbances and improve patient outcomes.